STUDYING THE ELEMENTS AND FACTORS THAT CONTRIBUTED TO THE SUCCESS OF SOUTH KOREA'S HALLYU WAVE - Srisooksai, Dhanakron; Petprasert , Narong (RMUTT Global Business and Economics Review, 2026)
This research is a documentary study aiming to examine the elements and the interrelationships of factors influencing the success of the Hallyu wave's spread to other countries, from the perspective of political economy and international political economy. The research findings revealed that the success of the Hallyu wave comprised seven components, ranked from most to least impactful, as follows: 1) Culture, 2) Stability, 3) Communication, 4) Public and Private Investment, 5) Finance and Banking, 6) Beliefs, and 7) Knowledge and Technology. This research will be used to provide concrete recommendations for promoting Thailand's soft power internationally.